The Development of a Culturally Relevant, Theoretically Driven HPV Prevention Intervention for Urban Adolescent Females and Their Parents/Guardians. Issue 4 (July 2013) - Brawner, Bridgette M.; Baker, Jillian L.; Voytek, Chelsea D.; Leader, Amy; Cashman, Rebecca R.; Silverman, Randee; Peter, Nadja; Buchner, Bradley J.; Barnes, Christopher A.; Jemmott, Loretta S.; Frank, Ian
Human papillomavirus (HPV) is the most common sexually transmitted infection in the United States, accounting for the large majority of cervical cancer and anogenital warts cases. Two HPV vaccines are currently licensed and recommended for women and girls. However, vaccination rates have been suboptimal, with evidence of disparities influencing both uptake and series completion among African American and Hispanic adolescents. There has been a dearth of theory-based, behavioral interventions targeted to prevent HPV infection and increase HPV vaccine uptake among urban adolescents. This article describes the development of two skills-based intervention curricula aimed to increase HPV prevention and vaccination among low-income urban adolescent females 9 to 18 years old. Guided by the theory of planned behavior, elicitation research was conducted to elucidate the social psychological factors that underlie HPV vaccination intentions ( N = 141). The findings were subsequently used to identify theoretical mediators of behavioral change to drive the intervention. Culturally relevant strategies to promote HPV vaccination were translated into the curricula content. Both curricula were designed to motivate and empower participants to reduce risk of being infected with HPV. Targeting theoretical mediators of behavioral change, derived from the voices of the community, may prove to be successful in increasing HPV vaccination and preventing HPV.